1998
DOI: 10.1007/bf01691130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of six commercial systems for identification of medically important yeasts

Abstract: Six commercially available systems for the identification of yeasts were evaluated using 133 clinical isolates and four reference strains that had been previously identified by conventional methods and 19 recent clinical isolates that had been identified by the ID32C system (bioMérieux, France). The total identification rates (TIR) established for the total number of strains tested and the database identification rates (DBIR) established for the strains included in the respective manufacturer databases were bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…The main characteristics of the 26 studies (32-57), which were published between 1993 and 2014, are shown in Table 1 (see also Table S2 in the supplemental material). Among the 26 studies, 12 (32-34, 36-38, 40-43, 45, 54) reported on the identification performance of the AuxaColor system, 5 (35,38,39,43,54) reported on the identification performance of the API ID32C system, and 13 (44,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) reported on the identification performance of the Vitek 2 system operating with the ID-YST (fluorimetric) card (44,(46)(47)(48)(49) and/or the YST (colorimetric) card (47,48,(50)(51)(52)(53)(54)(55)(56)(57); among them, three were direct-comparison studies, of which two were between the AuxaColor and API ID32C systems (38,43) and one was among the AuxaColor, API ID32C, and Vitek 2 systems (54). Two studies evaluating the Vitek 2 system compared the colorimetric YST card with the older fluorimetric ID-YST card (47,48); however, we decided to include the results of these studies only with respect to the YST card.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the 26 studies (32-57), which were published between 1993 and 2014, are shown in Table 1 (see also Table S2 in the supplemental material). Among the 26 studies, 12 (32-34, 36-38, 40-43, 45, 54) reported on the identification performance of the AuxaColor system, 5 (35,38,39,43,54) reported on the identification performance of the API ID32C system, and 13 (44,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) reported on the identification performance of the Vitek 2 system operating with the ID-YST (fluorimetric) card (44,(46)(47)(48)(49) and/or the YST (colorimetric) card (47,48,(50)(51)(52)(53)(54)(55)(56)(57); among them, three were direct-comparison studies, of which two were between the AuxaColor and API ID32C systems (38,43) and one was among the AuxaColor, API ID32C, and Vitek 2 systems (54). Two studies evaluating the Vitek 2 system compared the colorimetric YST card with the older fluorimetric ID-YST card (47,48); however, we decided to include the results of these studies only with respect to the YST card.…”
Section: Resultsmentioning
confidence: 99%
“…The commercially available yeast identification methods (1,2,4,5,9,(13)(14)(15)17) have easily identified the common yeast species; however, uncommon and newly described species present a significant challenge. Phenotypic characteristics often cannot distinguish between species that have overlapping phenotypic characters.…”
mentioning
confidence: 99%
“…These results match those achieved with slower trehalase-based tests (4,12,19). Widely used commercial yeast identification systems such as API20CAUX, Auxacolor, Fungichrom, and Vitek YBC often perform less well than GLABRATA RTT (2,8).…”
mentioning
confidence: 99%